Inhibitor of apoptosis proteins as therapeutic targets in multiple myeloma - Ramakrishnan, V; Painuly, U; Kimlinger, T; Haug, J; Rajkumar, S V; Kumar, S (Leukemia, 2014)
The inhibitor of apoptosis (IAP) proteins have a critical role in the control of apoptotic machinery, and has been explored as a therapeutic target. Here, we have examined the functional importance of IAPs in multiple myeloma (MM) by using a Smac (second mitochondria-derived activator of caspases)-mimetic LCL161. We observed that LCL161 was able to potently induce apoptosis in some MM cell lines but not in others. Examining the levels of X-linked inhibitor of apoptosis protein (XIAP), cellular inhibitor of apoptosis protein 1 (cIAP1) and cellular inhibitor of apoptosis protein 2 (cIAP2) post LCL161 treatment indicated clear downregulation of both XIAP activity and cIAP1 levels in both the sensitive and less sensitive (resistant) cell lines. cIAP2, however, was not downregulated in the cell line resistant to the drug. Small interfering RNA-mediated silencing of cIAP2 significantly enhanced the effect of LCL161, indicating the importance of downregulation of all IAPs simultaneously for induction of apoptosis in MM cells. LCL161 induced marked up regulation of the Jak2/Stat3 pathway in the resistant MM cell lines. Combining LCL161 with a Jak2-specific inhibitor resulted in synergistic cell death in MM cell lines and patient cells. In addition, combining LCL161 with death-inducing ligands clearly showed that LCL161 sensitized MM cells to both Fas-ligand and TRAIL.
Keywords: nádorové mikroprostředí; cílená molekulární terapie; proteiny regulující apoptózu; Enzyme Activation; TNF-Related Apoptosis-Inducing Ligand; protinádorové látky; Cell Line, Tumor; Cell Proliferation; Fas Ligand Protein; Janus kinasa 2; signální transdukce; protein TRAIL; Cell Death; Janus Kinase 2; buněčná smrt; Apoptosis Regulatory Proteins; Multiple Myeloma; ligand Fas; Signal Transduction; Thiazoles; Caspases; kaspasy; thiazoly; lidé; Humans; NF-kappa B; Molecular Targeted Therapy; aktivace enzymů; apoptóza; proliferace buněk; STAT3 Transcription Factor; transkripční faktor STAT3; nádorové buněčné linie; mnohočetný myelom; Tumor Microenvironment; Apoptosis; Antineoplastic Agents